Separated 3D printing of continuous carbon fiber reinforced thermoplastic polyimide. (June 2019) - Ye, Wenli; Lin, Guoqiang; Wu, Wenzheng; Geng, Peng; Hu, Xue; Gao, Zhiwei; Zhao, Ji
Abstract: Manufacturing difficulties, poor strength and foaming result from the high temperature that is used in thermoplastic polyimide (TPI) 3D printing and the high viscosity and water absorption by the TPI. To overcome these difficulties, the water absorption of pure TPI 3D printed filaments and short-fiber TPI composites were analyzed. The relationship between the drying time of pure TPI 3D printed filaments and the tensile strength of 3D printed specimens was studied. The effects of 3D printing speeds, layer thicknesses and filling rates on the tensile strength of the 3D printed parts were studied employed pure TPI, original continuous carbon fiber reinforced TPI (OCC) and separated continuous carbon fiber reinforced TPI (SCC). The mechanical properties of the continuous-carbon-fiber reinforced TPI were tested on TPI 3D printed samples with or without continuous fiber reinforcement. The SCC improved the success rate of the continuous-carbon-fiber reinforced TPI by 3D printing and enhanced the interfacial bonding strength between the continuous carbon fiber and the TPI matrix. The tensile strength of the continuous carbon fiber reinforced TPI was 158% higher than that of the OCC. A strong bonding surface formed between the continuous carbon fiber and the TPI plastic matrix. The tensile and bending strengths of the the SCC samples were 214% and 167% higher than those of pure TPI. SCC 3D printing can enable the printing of complex parts with an excellent interfacial bonding performance, mechanical properties and high temperature resistance, which can be used in the aerospace industry and other fields.